Exercise

Solve the following equation. -52=34z+12 \text{-} \dfrac{5}{2}=\dfrac{3}{4}z+\dfrac{1}{2}

Answer

z=-4z=\text{-}4

Hint

Solution

To solve the equation, we need to transfer the zz terms to one side and the constant terms to the other.

-52=34z+12\text{-} \dfrac{5}{2}=\dfrac{3}{4}z+\dfrac{1}{2}
-62=34z\text{-} \dfrac{6}{2}=\dfrac{3}{4}z
-3=34z\text{-}3=\dfrac{3}{4}z
-1=14z\text{-}1=\dfrac{1}{4}z
-4=z\text{-}4=z
z=-4z=\text{-}4

The solution of the equation then is z=-4.z=\text{-}4.

{{ 'ml-template-article-upsell1' | message }}

{{ 'ml-template-article-upsell2' | message }}

{{ 'ml-template-article-upsell3' | message }}